The tenants of East Harlem - Sharman, Russell Leigh, 1972- (University of California Press, 2006)
Rich with the textures and rhythms of street life, The Tenants of East Harlem is an absorbing and unconventional biography of a neighborhood told through the life stories of seven residents whose experiences there span nearly a century. Modeled on the ethnic distinctions that divide the community, the book portrays the old guard of East Harlem: Pete, one of the last Italian holdouts; José, a Puerto Rican; and Lucille, an African American. Side by side with these representatives of a century of ethnic succession are the newcomers: Maria, an undocumented Mexican; Mohamed, a West African e.